Promoting Self-Regulation in Health Among Vulnerable Brazilian Children: Protocol Study - Mattos, Luciana B.; Mattos, Marina B.; Barbosa, Ana P. O.; Bauer, Mariana da Silva; Strack, Maina H.; Rosário, Pedro; Reppold, Caroline T.; Magalhães, Cleidilene R. (Frontiers in Psychology, 2018)
The Health and Education Ministries of Brazil launched the Health in School Program (Programa Saúde na Escola - PSE) in 2007. The purpose of the PSE is twofold: articulate the actions of the education and health systems to identify risk factors and prevent them; and promote health education in the public elementary school system. In the health field, the self-regulation (SR) construct can contribute to the understanding of life habits which can affect the improvement of individuals' health. This research aims to present a program that promotes SR in health (SRH). This program (PSRH) includes topics on healthy eating and oral health from the PSE; it is grounded on the social cognitive framework and uses story tools to train 5th grade Brazilian students in SRH. The study consists of two phases. In Phase 1, teachers and health professionals participated in a training program on SRH, and in Phase 2, they will be expected to conduct an intervention in class to promote SRH. The participants were randomly assigned into three groups: the Condition I group followed the PSE program, the Condition II group followed the PSRH (i.e. PSE plus the SRH program), and the control group (CG) did not enroll in either of the health promotion programs. For the baseline of the study, the following measures and instruments were applied: Body Mass Index (BMI), Simplified Oral Hygiene Index (OHI-S), Previous Day Food Questionnaire (PFDQ), and Declarative Knowledge for Health Instrument. Data indicated that the majority are eutrophic children, but preliminary outcomes showed high percentages of children that are overweight, obese and severely obese. Moreover, participants in all groups reported high consumption of ultraprocessed foods (e.g., soft drinks, artificial juices and candies). Oral health data from the CI and CII groups showed a prevalence of regular oral hygiene, while the CG presented good oral hygiene. The implementation of both PSE and PSRH are expected to help reduce health problems in school, as well as the public expenditures with children’s health (e.g., Obesity and oral diseases).